Asphalt-based microcrystalline hard carbon material as well as preparation method and application thereof

Through the heat condensation and oxidative crosslinking of low-temperature asphalt, high-capacity, large-magnification and long-circulation asphalt-based microcrystalline hard carbon materials are prepared, solving the shortcomings of hard carbon materials in terms of circulation performance and achieving more efficient battery performance.

CN119143112AActive Publication Date: 2024-12-17SHIJIAZHUANG SHANGTAI TECH CO LTD

Patent Information

Application Number
CN202411340554.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-17
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing hard carbon materials have shortcomings in circulation performance, and it is difficult to take into account both high capacity, large ratio and long cycles. The carbonization process has limited structural regulation effect and cannot meet market demand.

Method used

Low-temperature asphalt is used as raw material to form mesophase asphalt with a certain carbon microcrystalline structure by heat condensation, and oxidation crosslinking and carbonization are carried out to prepare asphalt-based microcrystalline hard carbon materials with high capacity, large-magnification and long cycles.

Benefits of technology

By controlling the thermal polycondensation and oxidation crosslinking conditions, the carbon microcrystalline structure is regulated, the circulation performance of hard carbon materials and the energy density and endurance of the battery are improved, and the effects of high capacity, large magnification and long cycles are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of hard carbon materials, and particularly discloses an asphalt-based microcrystalline hard carbon material as well as a preparation method and application thereof. The preparation method comprises the following steps: in an inert atmosphere, carrying out thermal polycondensation reaction on low-temperature asphalt at the temperature of 300-550 DEG C and the pressure of 0.01-10 MPa to obtain mesophase asphalt; the softening point of the low-temperature asphalt is 18-48 DEG C; in an oxygen-containing atmosphere, carrying out oxidation crosslinking on the mesophase pitch to obtain a hard carbon precursor; and performing carbonization treatment on the hard carbon precursor in an inert atmosphere to obtain the asphalt-based microcrystalline hard carbon material. According to the preparation method, the low-temperature pitch is creatively used as a raw material, the size of carbon microcrystals is convenient to regulate and control, the cost is low, the mesophase pitch with a certain carbon microcrystal structure is formed through thermal polycondensation, the mesophase pitch is subjected to oxidation crosslinking, the interlayer distance of carbon layers is enlarged, and finally the pitch-based microcrystal hard carbon material with high capacity, high rate and long circulation is prepared. The method has high market application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hard carbon materials, and in particular to a pitch-based microcrystalline hard carbon material and a preparation method and application thereof. Background Art

[0002] With the rapid development of lithium-ion batteries and the shortage of lithium resources, sodium-ion batteries, which have similar electrochemical properties and abundant content to lithium-ion batteries, have gradually shown good commercial potential. + The ionic radius is larger than Li + The ionic radius of Na is about 55% larger and the diffusion kinetics are slow, so Na + Insertion and extraction from battery materials are more difficult. Sodium storage behavior typically manifests itself in a slope potential region (0.1V-2.8V) and a plateau region (0.01V-0.10V). The region below 1.0V is generally the most beneficial contributor to energy density, but its actual contribution is typically less than 50%. To improve the reversible capacity and rate performance of sodium-ion batteries and increase the utilization of reversible capacity (below 1.0V), the design and synthesis of hard carbon structures has become a major breakthrough.

[0003] At present, the research on hard carbon materials focuses more on high capacity and high first efficiency, but not enough attention is paid to long cycle. Ways to obtain high-performance hard carbon negative electrode materials include structural engineering, defect engineering, surface engineering and pre-sodiumization. Among them, structural engineering mainly involves morphology control and pore design. The work of pore control is largely subject to the intrinsic composition, structure and properties of the precursor. At the same time, the process of control engineering needs to take into account factors such as the first coulombic efficiency of hard carbon and hard carbon cycle performance. The overall room for improvement is limited. For example, the control of the size of the hard carbon microcrystalline structure that affects the hard carbon cycle performance is more achieved by controlling the carbonization process of hard carbon. However, the carbonization process has little effect on materials with fixed structures. Therefore, the carbonization process can only take into account some technical requirements (such as high capacity and first coulombic efficiency), but cannot achieve the technical requirements of long cycle of hard carbon materials. Therefore, there is an urgent need to develop a hard carbon material that takes into account high capacity, large rate and long cycle at the same time to meet market demand. Summary of the Invention

[0004] In response to the above problems, the present invention provides a pitch-based microcrystalline hard carbon material, a preparation method and application thereof. Low-temperature asphalt is used as raw material, and an intermediate phase asphalt with a certain carbon microcrystalline structure (structurally ordered) is formed through thermal polycondensation. The intermediate phase asphalt is oxidatively cross-linked to expand the interlayer spacing of the carbon layer, and finally a pitch-based microcrystalline hard carbon material with high capacity, large rate and long circulation is prepared.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a pitch-based microcrystalline hard carbon material, comprising the following steps: S1, in an inert atmosphere, subjecting low-temperature asphalt to a thermal polycondensation reaction at 300°C to 550°C and 0.01MPa to 10MPa to obtain mesophase asphalt; The softening point of the low-temperature asphalt is 18°C ​​to 48°C; S2, oxidatively crosslinking the mesophase pitch in an oxygen-containing atmosphere to obtain a hard carbon precursor; S3, carbonizing the hard carbon precursor under an inert atmosphere to obtain a pitch-based microcrystalline hard carbon material.

[0006] Compared with the prior art, the preparation method of asphalt-based microcrystalline hard carbon material provided by the present invention uses low-temperature asphalt as the main active substance to store alkali metal ions. The aromatic component content of low-temperature asphalt is very low, which is convenient for regulating the size of carbon microcrystals and has lower cost. Compared with medium and high temperature asphalt raw materials, since the aromatic component content of low-temperature asphalt is very low, polymerization and cross-linking are more difficult. The present invention controls the temperature and pressure of the thermal condensation reaction to obtain anisotropic intermediate phase asphalt with a certain carbon microcrystal structure. Compared with the hard carbon material with disordered structure, the irreversible capacity loss of the intermediate phase asphalt during circulation is reduced, and the cycle performance is greatly improved. Then, the surface and edge of the intermediate phase asphalt are oxidatively cross-linked to expand the interlayer spacing of the carbon layer, and further obtain a carbon microcrystalline material with disordered outer layer structure and ordered internal structure as a hard carbon precursor. Combined with the relatively disordered combination between carbon microcrystals, the slope area and platform area of ​​the battery material can store more alkali metal ions and respond faster to the diffusion of alkali metal ions at a high rate, thereby improving the capacity and rate performance of the microcrystalline hard carbon material. Finally, through carbonization treatment, a high-capacity, high-rate and long-cycle asphalt-based microcrystalline hard carbon material is obtained.

[0007] The preparation method of the pitch-based microcrystalline hard carbon material provided by the present invention creatively uses low-temperature pitch as raw material. The raw material is easily available and low in cost. The process operation is simple and easy, and it is suitable for large-scale production and has high market application value.

[0008] Preferably, in S3, before the carbonization treatment, the process further comprises: Adding high softening point pitch to the hard carbon precursor, performing granulation, coating and sphericalization treatment to obtain a coated hard carbon particle precursor; The softening point of the high softening point asphalt is 180°C to 320°C.

[0009] The present invention coats the surface of the hard carbon precursor with high softening point asphalt. The high softening point asphalt has a large molecular weight and is regular and orderly. The hard carbon precursor coated with the high softening point asphalt has fewer defects, which reduces the specific surface area of ​​the microcrystalline hard carbon material, thereby reducing the irreversible capacity of the microcrystalline hard carbon material and increasing the first coulomb efficiency of the microcrystalline hard carbon material. At the same time, the compaction density of the microcrystalline hard carbon material is improved, so that the microcrystalline hard carbon negative electrode can store more charge under the same volume, further optimizing its energy storage performance, thereby improving the energy density and endurance of the battery.

[0010] Preferably, in S1, the softening point of the low-temperature asphalt is 20°C~45°C.

[0011] Preferably, in S1, the coking value of the low-temperature asphalt is 15wt%~50wt%, more preferably 18wt%~48wt%, and even more preferably 25wt%~40wt%.

[0012] For example, in S1, the low-temperature asphalt is selected from petroleum asphalt or coal asphalt.

[0013] Preferably, in S1, before the thermal polycondensation reaction, the low-temperature asphalt needs to be dried.

[0014] For example, in S1, the drying temperature is 150° C. to 300° C., and the drying time is 1 hour to 1.5 hours.

[0015] The present invention first dries the low-temperature asphalt to remove moisture in the low-temperature asphalt, which is beneficial to the subsequent thermal polycondensation reaction.

[0016] Preferably, in S1, the temperature is raised to 300°C~550°C by programmed temperature rise, with a heating rate of 1°C / min~20°C / min (more preferably 1°C / min~18°C / min, more preferably 1°C / min~10°C / min).

[0017] Preferably, in S1, the temperature of the thermal polycondensation reaction is 350° C. to 500° C., and the pressure is 0.01 MPa to 8 MPa (more preferably 0.5 MPa to 3 MPa).

[0018] Preferably, in S1, the thermal polycondensation reaction time is 0.5 h to 30 h, more preferably 1 h to 30 h, and more preferably 2 h to 20 h.

[0019] Preferably, in S1, the inert atmosphere is selected from argon atmosphere or nitrogen atmosphere, and the gas flow rate is 10 mL / min~200 mL / min, more preferably 10 mL / min~180 mL / min, more preferably 15 mL / min~120 mL / min, and further preferably 20 mL / min~80 mL / min.

[0020] By controlling the conditions of the thermal polycondensation reaction, the present invention improves the thermal conversion efficiency of low-temperature asphalt and enhances the quality of mesophase asphalt. By regulating the conditions of the thermal polycondensation reaction, the present invention can adjust the orderliness of the mesophase asphalt structure. Generally, the lower the softening point of the low-temperature asphalt, the lower the molecular activity, the lower the thermal polycondensation temperature and the longer the reaction time. The higher the thermal polycondensation temperature, the faster the reaction rate, and the more ordered the microcrystalline structure of the mesophase asphalt. The higher the heating rate, the more disordered the microcrystalline structure of the mesophase asphalt.

[0021] Preferably, in S2, the oxygen content of the gas in the oxygen-containing atmosphere is ≥60% v / v, and the gas flow rate is 10 mL / min~200 mL / min.

[0022] Further preferably, in S2, the oxygen content of the gas in the oxygen-containing atmosphere is ≥65% v / v, and the gas flow rate is 20 mL / min to 200 mL / min (more preferably 50 mL / min to 100 mL / min).

[0023] Preferably, in S2, the temperature of the oxidative crosslinking is 150° C. to 380° C., and the time of the oxidative crosslinking is 0.5 h to 20 h.

[0024] More preferably, in S2, the temperature of the oxidative crosslinking is 180° C. to 350° C., and the time of the oxidative crosslinking is 1 h to 18 h (more preferably 1.5 h to 10 h).

[0025] By limiting the conditions for oxidative crosslinking, the present invention allows for mild oxidative crosslinking of the surface and edges of the mesophase pitch, effectively controlling the interlayer spacing of the carbon layers and, consequently, the adsorption and filling capacity in alkali metal ion batteries. To conserve energy, the oxidative crosslinking process in S2 does not require heating; instead, the residual heat from the thermal polycondensation reaction is utilized for mild oxidative crosslinking.

[0026] For example, in S2, after the oxidative crosslinking is completed, the process further includes: cooling to room temperature, filtering, and crushing to obtain a hard carbon precursor.

[0027] Further preferably, in S3, the mass ratio of the hard carbon precursor to the high softening point asphalt is (3~40):1, more preferably (3~30):1, and even more preferably (3~10):1.

[0028] Further preferably, in S3, the softening point of the high softening point asphalt is 190°C to 310°C, more preferably 220°C to 280°C.

[0029] Further preferably, in S3, the coking value of the high softening point asphalt is 45wt%~88wt%, more preferably 50wt%~85wt%, and even more preferably 60wt%~80wt%.

[0030] For example, in S3, the high softening point asphalt is selected from petroleum asphalt, coal asphalt or natural asphalt.

[0031] Further preferably, in S3, the conditions for the granulation, coating and spheroidization treatment include: temperature of 250° C. to 350° C., vacuum degree of 0.01 bar to 1 bar, and time of 2 h to 4 h.

[0032] More preferably, in S3, the conditions for the granulation, coating and spheroidization treatment include: temperature of 270° C. to 320° C., vacuum degree of 0.1 bar to 1 bar, and time of 2.5 h to 3.5 h.

[0033] For example, in S3, the granulation, coating and spheroidization treatment is carried out under stirring conditions at a rotation speed of 450 rpm to 550 rpm.

[0034] By limiting the softening point, coking value, dosage and granulation, coating and spheroidization treatment conditions of high-softening-point asphalt, the present invention can better compensate for the surface defects of the microcrystalline hard carbon material, reduce its specific surface area, and thus further reduce the irreversible capacity of the microcrystalline hard carbon material and improve the first coulombic efficiency.

[0035] Preferably, in S3, the inert atmosphere is selected from argon atmosphere or nitrogen atmosphere, and the gas flow rate is 0.01 L / min to 5 L / min, more preferably 0.1 L / min to 3 L / min, and more preferably 0.1 L / min to 1 L / min.

[0036] Preferably, in S3, the carbonization treatment conditions include: first heating to 350°C~550°C at a rate of 0.1°C / min~50°C / min, and keeping warm for 0.5h~10h; then heating to 750°C~1600°C at a rate of 0.5°C / min~20°C / min, and keeping warm for 0.5h~10h.

[0037] The pore volume of the microcrystalline hard carbon material after only one high-temperature carbonization treatment is too small, and the pore diameter is too large. The carbonization treatment of the present invention is carried out in two steps. First, the first carbonization treatment is carried out at a specific temperature to break the unstable structure in the precursor material and produce gas, thereby obtaining a fine pore diameter and increasing the pore volume. Then, the second carbonization treatment is carried out at a specific temperature. The high-temperature gas production has a greater damage to the pore diameter of the material, causing the material to be further carbonized. Compared with a single high-temperature carbonization treatment, the present invention increases the pore volume of the asphalt-based microcrystalline hard carbon material through a two-step carbonization treatment under specific conditions, which is more conducive to the shuttle of alkali metal ions in the asphalt-based microcrystalline hard carbon material, thereby improving the pore volume and rate of the battery material.

[0038] Further preferably, in S3, the carbonization treatment conditions include: first heating to 350°C~550°C at a rate of 1°C / min~40°C / min, and keeping warm for 0.5h~8h; then heating to 750°C~1600°C at a rate of 2°C / min~15°C / min, and keeping warm for 0.5h~8h.

[0039] More preferably, in S3, the carbonization treatment conditions include: first heating to 400°C~500°C at a rate of 2°C / min~20°C / min, and keeping warm for 0.6h~5h; then heating to 800°C~1500°C at a rate of 4°C / min~10°C / min, and keeping warm for 1h~6h.

[0040] For example, in S3, after the carbonization treatment is completed, the process further includes: cooling to room temperature, crushing, and obtaining a pitch-based microcrystalline hard carbon material.

[0041] Preferably, the particle size of the pitch-based microcrystalline hard carbon material is D 50 =4μm~18μm.

[0042] In a second aspect, the present invention provides a pitch-based microcrystalline hard carbon material, which is prepared by the above-mentioned method for preparing a pitch-based microcrystalline hard carbon material.

[0043] The pitch-based microcrystalline hard carbon material provided by the present invention has an ordered structure of larger carbon microcrystals inside, low irreversible lithium or sodium insertion capacity, and a disordered stacking structure between the carbon microcrystals that expands the filling capacity; the external oxygen-containing disordered structure has the function of adsorption and filling capacity, so that the pitch-based microcrystalline hard carbon material has both high capacity and long cycle characteristics; the large oxygen-containing interlayer spacing increases the diffusion rate of alkali metal ions, and can withstand a higher rate of current density.

[0044] In addition, when high softening point asphalt is used for coating, the surface defects of the microcrystalline hard carbon material can be reduced, the irreversible capacity of the microcrystalline hard carbon material can be reduced, and the asphalt-based microcrystalline hard carbon material can have high first-effect characteristics.

[0045] In a third aspect, the present invention further provides an application of the pitch-based microcrystalline hard carbon material in an alkali metal ion battery, wherein the alkali metal ion battery is selected from at least one of a sodium ion battery and a lithium ion battery.

[0046] Preferably, the pitch-based microcrystalline hard carbon material is the positive electrode material of the alkali metal ion battery.

[0047] The results of the examples show that when the pitch-based microcrystalline hard carbon material provided by the present invention is applied to sodium ion batteries, the gram capacity can reach more than 220 mA·h / g, the first coulombic efficiency can reach more than 60%, the 6C / 1C capacity retention rate can reach more than 60%, the capacity retention rate after 50 cycles at 1C can reach more than 60%, and the carbonization yield can reach more than 40%. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0049] The present invention provides a method for preparing a pitch-based microcrystalline hard carbon material, comprising the following steps: S1, in an inert gas atmosphere, subjecting low-temperature asphalt to a thermal polycondensation reaction at 300°C to 550°C and 0.01MPa to 10MPa to obtain mesophase asphalt; The softening point of the low-temperature asphalt is 18°C ​​to 48°C; S2, oxidatively crosslinking the mesophase pitch in an oxygen-containing gas atmosphere to obtain a hard carbon precursor; S3, adding high softening point pitch to the hard carbon precursor, performing granulation, coating and sphericalization treatment to obtain a coated hard carbon particle precursor; The high softening point asphalt has a softening point of 180°C to 320°C; S4, carbonizing the coated hard carbon particle precursor under an inert gas atmosphere to obtain a pitch-based microcrystalline hard carbon material.

[0050] SP represents the coking value, and CV represents the coking value.

[0051] In order to better illustrate the present invention, further examples are given below.

[0052] Example 1 This embodiment provides a method for preparing a pitch-based microcrystalline hard carbon material, comprising the following steps: Sa, 100g of low-temperature pitch (SP = 25°C, CV = 32wt%) was placed in a high-temperature reactor in a flask. The mixture was heated from room temperature to 200°C for drying and held at this temperature for 1 hour to remove moisture. Argon was introduced at a flow rate of 50mL / min. The dried low-temperature pitch was heated to 400°C at a rate of 1°C / min and subjected to a thermal polycondensation reaction at 1MPa for 6 hours. After the reaction, the resulting mesophase pitch was immediately transferred to a round-bottom flask. The gas was switched to an oxygen-containing gas with an oxygen content of 65% v / v via a glass tube at a flow rate of 80mL / min. Oxidative crosslinking was carried out for 2 hours, followed by cooling to room temperature, filtration, and crushing to obtain a hard carbon precursor.

[0053] Sb, transfer the hard carbon precursor to a high-temperature fusion granulator, add high softening point asphalt (SP=260℃, CV=73wt%), the mass ratio of hard carbon precursor to high softening point asphalt is 3:1, and carry out granulation, coating and spheroidization treatment at 290℃ and 0.99bar, stir and keep warm for 3h to obtain a coated hard carbon particle precursor.

[0054] Sc, the coated hard carbon particle precursor was transferred to the reactor, and in an argon atmosphere with a flow rate of 0.15L / min, the temperature was first raised to 460℃ at a rate of 5℃ / min for the first carbonization treatment, and kept warm for 1h; then the temperature was raised to 1350℃ at a rate of 7℃ / min for the second pre-carbonization treatment, and kept warm for 3h; cooled to room temperature, crushed, and the particle size was D 50 =6μm pitch-based microcrystalline hard carbon material.

[0055] Example 2 This embodiment provides a method for preparing a pitch-based microcrystalline hard carbon material, comprising the following steps: Sa, 100g of low-temperature pitch (SP = 30°C, CV = 40wt%) was placed in a high-temperature reactor in a flask and heated from room temperature to 220°C for drying. This temperature was then maintained for 1 hour to remove moisture. Argon was introduced at a flow rate of 100mL / min. The dried low-temperature pitch was heated to 450°C at a rate of 5°C / min and subjected to a thermal polycondensation reaction at 2MPa for 5 hours. After the reaction, the resulting mesophase pitch was immediately transferred to a round-bottom flask. The gas was switched to an oxygen-containing gas with an oxygen content of 60% v / v via a glass tube at a flow rate of 100mL / min. Oxidative crosslinking was carried out for 3 hours, followed by cooling to room temperature, filtration, and crushing to obtain a hard carbon precursor.

[0056] Sb, transfer the hard carbon precursor to a high-temperature fusion granulator, add high softening point asphalt (SP = 310 ° C, CV = 85wt%), the mass ratio of hard carbon precursor to high softening point asphalt is 10:1, and carry out granulation, coating and spheroidization treatment at 340 ° C and 0.50 bar, stir and keep warm for 2 hours to obtain a coated hard carbon particle precursor.

[0057] Sc, the coated hard carbon particle precursor was transferred to a reactor, and in an argon atmosphere with a flow rate of 0.1 L / min, the temperature was first raised to 530 ° C at a rate of 45 ° C / min for the first carbonization treatment, and the temperature was kept at this temperature for 6 h; then the temperature was raised to 1600 ° C at a rate of 18 ° C / min for the second pre-carbonization treatment, and the temperature was kept at this temperature for 0.8 h; cooled to room temperature, crushed, and the particle size was D 50 =8μm pitch-based microcrystalline hard carbon material.

[0058] Example 3 This embodiment provides a method for preparing a pitch-based microcrystalline hard carbon material, comprising the following steps: Sa, 100g of low-temperature pitch (SP = 20°C, CV = 20wt%) was placed in a flask-shaped high-temperature reactor and heated from room temperature to 180°C for drying, then held at this temperature for 1.5 hours to remove moisture. Nitrogen was introduced at a flow rate of 30mL / min. The dried low-temperature pitch was heated to 350°C at a rate of 10°C / min and subjected to a thermal polycondensation reaction at 0.5MPa for 8 hours. After the reaction, the resulting mesophase pitch was immediately transferred to a round-bottom flask. The gas was switched to an oxygen-containing gas with an oxygen content of 70% v / v via a glass tube at a flow rate of 50mL / min. Oxidative crosslinking was carried out for 1.5 hours, followed by cooling to room temperature, filtration, and crushing to obtain a hard carbon precursor.

[0059] Sb, transfer the hard carbon precursor to a high-temperature fusion granulator, add high softening point asphalt (SP = 190 ° C, CV = 48wt%), the mass ratio of hard carbon precursor to high softening point asphalt is 30:1, and carry out granulation, coating and spheroidization treatment at 260 ° C and 0.1 bar. Stir and keep warm for 4 hours to obtain a coated hard carbon particle precursor.

[0060] Sc, the coated hard carbon particle precursor was transferred to a reactor, and in a nitrogen atmosphere with a flow rate of 5L / min, the temperature was first raised to 360℃ at a rate of 0.3℃ / min for the first carbonization treatment, and kept warm for 0.6h; then the temperature was raised to 780℃ at a rate of 0.7℃ / min for the second pre-carbonization treatment, and kept warm for 8h; cooled to room temperature, crushed, and the particle size was D 50 =10μm pitch-based microcrystalline hard carbon material.

[0061] Example 4 This embodiment provides a method for preparing a pitch-based microcrystalline hard carbon material, comprising the following steps: Sa, 100g of low-temperature pitch (SP = 18°C, CV = 20wt%) was placed in a high-temperature reactor in a flask. The mixture was heated from room temperature to 200°C for drying and held at this temperature for 1 hour to remove moisture. Argon was introduced at a flow rate of 200mL / min. The dried low-temperature pitch was heated to 300°C at a rate of 18°C / min and subjected to a thermal polycondensation reaction at 0.01MPa for 20 hours. After the reaction, the resulting mesophase pitch was immediately transferred to a round-bottom flask. The gas was switched to an oxygen-containing gas with an oxygen content of 90% v / v via a glass tube at a flow rate of 10mL / min. Oxidative crosslinking was carried out for 10 hours, followed by cooling to room temperature, filtration, and crushing to obtain a hard carbon precursor.

[0062] Sb~Sc, the same as in Example 1, no further details are given. The final particle size is D 50 =16μm pitch-based microcrystalline hard carbon material.

[0063] Example 5 This embodiment provides a method for preparing a pitch-based microcrystalline hard carbon material, comprising the following steps: Sa, 100g of low-temperature pitch (SP = 45°C, CV = 48wt%) was placed in a high-temperature reactor in a flask and heated from room temperature to 200°C for drying. This temperature was then maintained for 1 hour to remove moisture. Argon was introduced at a flow rate of 15mL / min. The dried low-temperature pitch was heated to 530°C at a rate of 1.5°C / min and subjected to a thermal polycondensation reaction at 10MPa for 0.8h. Upon completion of the reaction, the resulting mesophase pitch was immediately transferred to a round-bottom flask. The gas was switched to an oxygen-containing gas with an oxygen content of 60% v / v via a glass tube at a flow rate of 200mL / min. Oxidative crosslinking was carried out for 10 hours, followed by cooling to room temperature, filtration, and crushing to obtain a hard carbon precursor.

[0064] Sb~Sc, the same as in Example 1, no further details are given. The final particle size is D 50 =4μm pitch-based microcrystalline hard carbon material.

[0065] Example 6 This embodiment provides a method for preparing a pitch-based microcrystalline hard carbon material, which is similar to that of Example 1, except that the oxygen content of the oxygen-containing gas in Sa is replaced with 40% v / v, the flow rate is replaced with 150 mL / min, and the oxidative crosslinking time is replaced with 5 h. The remaining operations are the same as those of Example 1 and will not be repeated here. The final particle size is D 50 =8μm pitch-based microcrystalline hard carbon material.

[0066] Example 7 This embodiment provides a method for preparing a pitch-based microcrystalline hard carbon material (without high softening point pitch coating), comprising the following steps: Sa, same as embodiment 1, no further details will be given.

[0067] The hard carbon precursor was transferred to a reactor and heated to 460°C at a rate of 5°C / min for the first carbonization treatment under an argon atmosphere with a flow rate of 0.15 L / min, and kept warm for 1 hour; then heated to 1350°C at a rate of 7°C / min for the second pre-carbonization treatment, and kept warm for 3 hours; cooled to room temperature, crushed, and obtained a particle size of D 50 =6μm pitch-based microcrystalline hard carbon material.

[0068] Example 8 This embodiment provides a method for preparing a pitch-based microcrystalline hard carbon material, comprising the following steps: Sa~Sb are the same as those in Example 1 and will not be described in detail.

[0069] Sc, the coated hard carbon particle precursor was transferred to a reactor, and the temperature was raised to 600℃ at a rate of 5℃ / min under an argon atmosphere with a flow rate of 0.15L / min for carbonization treatment, and kept at this temperature for 2h; cooled to room temperature, and crushed to obtain a particle size of D 50 =10μm pitch-based microcrystalline hard carbon material.

[0070] Example 9 This embodiment provides a method for preparing a pitch-based microcrystalline hard carbon material, comprising the following steps: Sa~Sb are the same as those in Example 1 and will not be described in detail.

[0071] Sc, the coated hard carbon particle precursor was transferred to a reactor, and pre-carbonized at a rate of 7 ° C / min to 1300 ° C in an argon atmosphere with a flow rate of 0.15 L / min, and kept at this temperature for 7 h; cooled to room temperature, crushed, and obtained a particle size of D 50 =10μm pitch-based microcrystalline hard carbon material.

[0072] Comparative Example 1 This comparative example provides a method for preparing a pitch-based microcrystalline hard carbon material, similar to Example 1, except that the low-temperature pitch in Sa is replaced with a medium-temperature pitch (SP = 60°C, CV = 32 wt%). The remaining conditions are the same as in Example 1 and are not further described.

[0073] Comparative Example 2 This comparative example provides a method for preparing a pitch-based microcrystalline hard carbon material, which is similar to Example 1, except that the temperature of the thermal polycondensation reaction is replaced with 200°C and the pressure is replaced with 0.01 MPa in Sa. The remaining conditions are the same as in Example 1 and are not repeated here.

[0074] Comparative Example 3 This comparative example provides a method for preparing a pitch-based microcrystalline hard carbon material, which is similar to Example 1, except that the temperature of the thermal polycondensation reaction is replaced with 700°C and the pressure is replaced with 10 MPa. The remaining conditions are the same as those in Example 1 and are not repeated here.

[0075] Comparative Example 4 This comparative example provides a method for preparing a pitch-based microcrystalline hard carbon material (omitting oxidative crosslinking), comprising the following steps: Sa, 100g of low-temperature pitch (SP = 25°C, CV = 32wt%) was placed in a high-temperature reactor in a flask and heated from room temperature to 200°C for drying. This temperature was maintained for 1 hour to remove moisture. Argon was introduced at a flow rate of 50mL / min. The dried low-temperature pitch was heated to 400°C at a rate of 1°C / min. A thermal polycondensation reaction was carried out at 1MPa and maintained for 6 hours to obtain the mesophase pitch.

[0076] Sb, transfer the intermediate phase pitch to a high-temperature fusion granulator, add high softening point pitch (SP = 260 ° C, CV = 73wt%), the mass ratio of hard carbon precursor to high softening point pitch is 3:1, and carry out granulation, coating and spheroidization treatment at 290 ° C and 0.99 bar. Stir and keep warm for 3 hours to obtain a coated hard carbon particle precursor.

[0077] Sc, same as embodiment 1, no further details are given.

[0078] Application Example 1 This application example provides a 2032 button-type battery, and the asphalt-based microcrystalline hard carbon material provided in Example 1 is selected as the positive electrode material.

[0079] The preparation method of 2032 button battery comprises the following steps: The positive electrode material, conductive agent SP, binder SBR and binder CMC were mixed in a mass ratio of 95.5:1.5:1.5:1.5. The positive electrode material, conductive agent SP, binder SBR and binder CMC were homogenized, coated and dried to obtain a positive electrode sheet with a compaction density of 1.05 g / cm 3 ; The negative electrode uses a sodium sheet with a thickness of 600μm, adds electrolyte, and is assembled into a 2032 button battery.

[0080] Application Examples 2~9 Application Examples 2 to 9 respectively provide a 2032 button-type battery, and the pitch-based microcrystalline hard carbon material provided in Examples 2 to 9 is respectively selected as the positive electrode material.

[0081] The preparation method of the 2032 button cell is the same as that in Application Example 1 and will not be described in detail.

[0082] Comparative Application Examples 1 to 4 Comparative Application Examples 1 to 4 respectively provide a 2032 button-type battery, and the pitch-based microcrystalline hard carbon material provided in Comparative Examples 1 to 4 is respectively selected as the positive electrode material.

[0083] The preparation method of the 2032 button cell is the same as that in Application Example 1 and will not be described in detail.

[0084] Charge and discharge test The following procedures were used to perform charge and discharge tests on 2032 button-type batteries for use cases 1-9 and comparative examples 1-4: In the 0-2.5V range, a constant current of 0.1C was applied to 2.5V, followed by a constant voltage of 2.5V until the current was less than 0.02C. After two cycles, the charge and discharge current was switched to a constant current of 1C. This cycle was repeated for 50 cycles before the 2032 button-type battery was removed. Rate tests were conducted using a constant 1C charge and discharge rate of 0.5C, 1C, 2C, 3C, 4C, 5C, or 6C, with five cycles at each discharge rate. The test results are shown in Table 1.

[0085] Table 1. Charge and discharge test results of 2032 button batteries in application examples and comparative application examples

[0086] In the table, "gram capacity" indicates the ratio of the capacity that can be released by the active material inside the battery to the mass of the active material; "6C / 1C capacity retention rate" indicates the ratio of the battery charging capacity at a 6C rate to the battery charging capacity at a 1C rate; "carbonization yield" is the ratio of the products before and after carbonization, that is, the mass ratio of the asphalt-based microcrystalline hard carbon material to the coated hard carbon particle precursor (or hard carbon precursor).

[0087] It can be seen from the test results in Table 1 that in the preparation method of asphalt-based microcrystalline hard carbon material provided by the present invention, the introduction of oxygen-containing gas for oxidative cross-linking can increase the disorder of the surface and edge of the intermediate phase asphalt, increase the interlayer spacing, and improve the hard carbon rate; through the disordered chaotic layer structure, the adsorption and filling capacity of sodium ions are increased, thereby improving the gram capacity; controlling the time of the thermal condensation reaction of low-temperature asphalt can regulate the size of the carbon microcrystals; using high-softening point asphalt for coating can reduce the specific surface area and surface defects of the microcrystalline hard carbon material, thereby improving the first coulomb efficiency.

[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a pitch-based microcrystalline hard carbon material, characterized in that: The following steps are involved: S1, in an inert atmosphere, subjecting low-temperature asphalt to a thermal polycondensation reaction at 300°C to 550°C and 0.01MPa to 10MPa to obtain a mesophase asphalt; The softening point of the low-temperature asphalt is 18°C ​​to 48°C; S2, oxidatively crosslinking the mesophase pitch in an oxygen-containing atmosphere to obtain a hard carbon precursor; S3, in an inert atmosphere, carbonizing the hard carbon precursor to obtain a pitch-based microcrystalline hard carbon material.

2. The method for preparing a pitch-based microcrystalline hard carbon material according to claim 1, characterized in that: In S3, before the carbonization treatment, the method further comprises: Adding high softening point asphalt to the hard carbon precursor, performing granulation, coating and spheroidization treatment to obtain a coated hard carbon particle precursor; The softening point of the high softening point asphalt is 180°C to 320°C.

3. The method for preparing a pitch-based microcrystalline hard carbon material according to claim 1, characterized in that: In S3, the carbonization treatment conditions include: first heating to 350°C~550°C at a rate of 0.1°C / min~50°C / min, and keeping warm for 0.5h~10h; then heating to 750°C~1600°C at a rate of 0.5°C / min~20°C / min, and keeping warm for 0.5h~10h.

4. The method for preparing a pitch-based microcrystalline hard carbon material according to claim 2, characterized in that: In S1, the coking value of the low-temperature asphalt is 15wt%~50wt%; In S3, the coking value of the high softening point asphalt is 45wt%~88wt%.

5. The method for preparing a pitch-based microcrystalline hard carbon material according to any one of claims 1 to 4, characterized in that: In S1, the temperature is raised to 300°C~550°C by programmed heating, and the heating rate is 1°C / min~20°C / min; In S1, the thermal polycondensation reaction time is 0.5h~30h.

6. The method for preparing a pitch-based microcrystalline hard carbon material according to any one of claims 1 to 4, characterized in that: In S2, the oxygen content of the gas in the oxygen-containing atmosphere is ≥60% v / v, and the flow rate of the gas is 10 mL / min to 200 mL / min; In S2, the temperature of the oxidative crosslinking is 150° C. to 380° C., and the time of the oxidative crosslinking is 0.5 h to 20 h.

7. The method for preparing a pitch-based microcrystalline hard carbon material according to claim 2, characterized in that: In S3, the mass ratio of the hard carbon precursor to the high softening point asphalt is (3-40):1; In S3, the conditions for the granulation, coating and spheroidization treatment include: temperature of 250° C. to 350° C., vacuum degree of 0.01 bar to 1 bar, and time of 2 h to 4 h.

8. A pitch-based microcrystalline hard carbon material, characterized in that: The asphalt-based microcrystalline hard carbon material is prepared by the preparation method of any one of claims 1 to 7.

9. The use of the pitch-based microcrystalline hard carbon material according to claim 8 in an alkali metal ion battery, characterized in that: The alkali metal ion battery is selected from at least one of a sodium ion battery and a lithium ion battery.

10. The use of the pitch-based microcrystalline hard carbon material in an alkali metal ion battery according to claim 9, characterized in that: The pitch-based microcrystalline hard carbon material is the positive electrode material of the alkali metal ion battery.

Citation Information

Patent Citations

  • Coal-based mesophase pitch, preparation method thereof, lithium ion battery negative electrode material and lithium ion battery

    CN114058397A

  • Preparation method and preparation device of coal pitch-based hard carbon negative electrode material

    CN115188952A

  • Graphite material with shell-core structure and preparation method thereof

    CN1923681A

Cited By

  • Asphalt-based sodium ion battery negative electrode material and preparation method thereof

    CN121020551A